2011
DOI: 10.1002/anie.201103599
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of 2‐Aryloxybenzaldehydes to 2‐Hydroxybenzophenones by Rhodium‐Catalyzed Cleavage of Aryloxy CO Bonds

Abstract: Lost in the shuffle: An unprecedented rearrangement of the title compounds proceeds by the simultaneous rhodium‐catalyzed cleavage of aryloxy CO and aldehyde CH bonds (see scheme). The reaction tolerates the presence of various catalytically reactive substituents such as aryl halides, nitrile, and esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Recently, ortho -functional group assisted cleavages of the C(Ar)–O bond of diaryl ethers via an intramolecular rearrangement have been reported. For example, Rao and Li developed a rhodium-catalyzed rearrangement of 2-aryloxybenzaldehydes involving cleavage of the C(Ar)–O bond of a diaryl ether, aldehyde C–H bond insertion, and an intramolecular chelation-assisted S N Ar process in the presence of a stoichiometric oxidant at high temperature 10 ( Scheme 1a ). Recently, the Glorius's group reported a N-heterocyclic carbene-catalyzed intramolecular arylation reactions of aldehyde C–H bonds involving cleavage of the C–O bonds of diaryl ethers ( Scheme 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ortho -functional group assisted cleavages of the C(Ar)–O bond of diaryl ethers via an intramolecular rearrangement have been reported. For example, Rao and Li developed a rhodium-catalyzed rearrangement of 2-aryloxybenzaldehydes involving cleavage of the C(Ar)–O bond of a diaryl ether, aldehyde C–H bond insertion, and an intramolecular chelation-assisted S N Ar process in the presence of a stoichiometric oxidant at high temperature 10 ( Scheme 1a ). Recently, the Glorius's group reported a N-heterocyclic carbene-catalyzed intramolecular arylation reactions of aldehyde C–H bonds involving cleavage of the C–O bonds of diaryl ethers ( Scheme 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Two major synthetic pathways can be followed in this transformation, namely, the well-known Friedel-Crafts reaction, 2 and the transition-metal-catalyzed C-H activation pathway. 3 However, classical Friedel-Crafts reactions often suffer from the harsh reaction condition and usage of air/water sensitive Lewis acid.…”
mentioning
confidence: 99%
“…(2‐Hydroxyphenyl)[3‐(trifluoromethyl)phenyl]methanone (2.21): Yellow liquid (113 mg, 85 %). R f (3 % ethyl acetate in hexane) = 0.41.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, rhodium‐catalyzed directed C–H arylations using diaryliodonium salts and 2‐(sulfonylamino)benzaldehyde have been reported . In addition, a few methods have been reported for the synthesis of 2‐hydroxybenzophenones , . A quick look into some of these methods revealed that rhodium‐catalyzed conditions provide an expanded scope in terms of synthetic utility and substrate reactivity.…”
Section: Introductionmentioning
confidence: 99%